Acid sphingomyelinase controls dopamine activity and responses to appetitive stimuli in mice - Kalinichenko, Liubov; Hammad, Lara; Reichel, Martin; Kohl, Zacharias; Gulbins, Erich; Kornhuber, Johannes; Müller, Christian P. (Brain Research Bulletin, 2019)
Alcohol use disorder and depression show a high comorbidity at clinical level with no treatment available selectively for this condition. A hyperfunction of acid sphingomyelinase (ASM) and resulting ceramide overload were recently identified as one pathway into this comorbidity. Here we analyzed the involvement of ASM, one of the main enzymes involved in ceramide synthesis, in the molecular control of monoaminergic systems in their basal activity and in response to pharmacological and natural reinforcers. The effects of alcohol and a palatable food on the extracellular levels of dopamine (DA), serotonin (5-HT), and noradrenaline (NE) were measured by in-vivo microdialysis in ASM overexpressing mice (tgASM). We found reduced basal extracellular DA levels in the nucleus accumbens (Nac) and dorsal hippocampus (DH) of tgASM mice with little effect on 5-HT and NE levels. In contrast, ASM overexpression potentiated the DA response to alcohol (2 g/kg, i.p.) in the DH and Nac, but reduced NE responses. DA and NE responses to a food stimulus were not altered in tgASM mice, but the Nac 5-HT response was enhanced.
CRIS-Team WoS Importer:2019-03-15

Adult neural precursor cells unaffected in animal models of DYT1 dystonia - Regensburger, Martin; Kohl, Zacharias; Grundmann, Kathrin; Winner, Beate; Riess, Olaf; Winkler, Jürgen (NeuroReport, 2009)
Hereditary dystonias in humans are frequently related to a specific mutation of the DYT1 gene that encodes torsinA. This mutation has been shown to disrupt neuronal cell migration during development. We compared adult neurogenesis, occurring in the hippocampus and the olfactory bulb, in transgenic mice overexpressing either the wild-type or mutant form of human torsinA. Neurogenesis was assessed by quantification of bromodeoxyuridine-labeled cells. Both transgenic mouse models displayed perinuclear inclusions in the brainstem and in mitral cells of the olfactory bulb, altered striatal dopamine levels, and behavioral abnormalities. However, both hippocampal and olfactory neurogenesis levels were unchanged compared with control animals. We conclude that overexpression of human wild-type or mutant torsinA does not affect the survival of adult newborn neurons. © 2009 Wolters Kluwer Health | Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2021-08-17
Keywords: Bromodeoxyuridine; Cellular plasticity; Doublecortin; Dystonia; DYT1; Hippocampus; Olfactory bulb; Subventricular zone; TorsinA

Ascending axonal degeneration of the corticospinal tract in pure hereditary spastic paraplegia: A cross-sectional DTI study - List, Julia; Kohl, Zacharias; Winkler, Jürgen; Marxreiter, Franz; Dörfler, Arnd; Schmidt, Manuel (Brain Sciences, 2019)
Objective: To identify structural white matter alterations in patients with pure hereditary spastic paraplegia (HSP) using high angular resolution diffusion tensor imaging (DTI). Methods: We examined 37 individuals with high resolution DTI, 20 patients with pure forms of hereditary spastic paraplegia and 17 age and gender matched healthy controls. DTI was performed using a 3 T clinical scanner with whole brain tract-based spatial statistical (TBSS) analysis of the obtained fractional anisotropy (FA) data as well as a region-of-interest (ROI)-based analysis of affected tracts including the cervical spinal cord. We further conducted correlation analyses between DTI data and clinical characteristics. Results: TBSS analysis in HSP patients showed significantly decreased fractional anisotropy of the corpus callosum and the corticospinal tract compared to healthy controls. ROI-based analysis confirmed significantly lower FA in HSP compared to controls in the internal capsule (0.77 vs. 0.80, p = 0.048), the corpus callosum (0.84 vs. 0.87, p = 0.048) and the cervical spinal cord (0.72 vs. 0.79, p = 0.003). FA values of the cervical spinal cord significantly correlated with disease duration. Conclusion: DTI metrics of the corticospinal tract from the internal capsule to the cervical spine suggest microstructural damage and axonal degeneration of motor neurons. The CST at the level of the cervical spinal cord is thereby more severely affected than the intracranial part of the CST, suggesting an ascending axonal degeneration of the CST. Since there is a significant correlation with disease duration, FA may serve as a future progression marker for assessment of the disease course in HSP.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Corticospinal tract; Diffusion tensor imaging; Fractional anisotropy; Hereditary spastic paraplegia; Tract-based spatial statistics (TBSS)

Association of early phenotypic behavioral alterations in human alpha-synuclein overexpressing transgenic rats with alpha-synuclein/huntingtin/amyloid-beta protein cross-seeding - Moceri, Sandra; Canneva, Fabio; Habermeyer, Johanna; Dobner, Julia; Schulze-Krebs, Anja; Puchades, Maja; Bjaalie, Jan G.; Kohl, Zacharias; Winkler, Jürgen; Timotius, Ivanna; Eskofier, Björn; Schilling, Stephan; et al. (Advances in Alzheimer's and Parkinson's Therapies an AAT-AD/PD Focus Meeting, 2018)

Biochemical markers of neurodegeneration in hereditary diffuse leucoencephalopathy with spheroids - Spitzer, Philipp; Kohl, Zacharias; Gölitz, Philipp; Coras, Roland; Blümcke, Ingmar; Brueck, Wolfgang; Dörfler, Arnd; Maihöfner, Christian (BMJ Case Reports, 2014)
Hereditary diffuse leucoencephalopathy with spheroids (HDLS) is a rare autosomal dominantly inherited disease with unknown pathophysiology. Diagnosis of neurodegenerative diseases is increasingly based on biomarkers. Although lumbar puncture is routinely performed during the diagnostic workup of HDLS, reports on alterations of neurodegeneration-specific biochemical markers have not been documented so far. We report a 35-year-old woman with clinical, radiological and neuropathological signs of HDLS. She suffered from a rapidly progressive frontal lobe syndrome. Brain MRI revealed diffuse leucoencephalopathy with predominant involvement of the periventricular white matter and corpus callosum. Although she was severely impaired and leucoencephalopathy was prominent, only cerebrospinal fluid total-? was moderately elevated. Other markers of neuronal (NSE) and astrocytic (S100B) damage were within normal range. Therefore, biochemical markers of central nervous system damage are not helpful in the diagnosis of HDL
EVALuna2:7264

Compensatory neuritogenesis of serotonergic afferents within the striatum of a transgenic rat model of Parkinson's disease - Stemick, Judith; Gauer, Carina; Wihan, Jeanette; Moceri, Sandra; Xiang, Wei; von Hörsten, Stephan; Kohl, Zacharias; Winkler, Jürgen (Brain Research, 2020)
The majority of patients with Parkinson's disease (PD) suffer from L-DOPA-induced dyskinesia (LID). Besides a dysfunctional dopaminergic system, changes of the serotonergic network may be linked to this severe and adverse symptom. Particularly, serotonergic neurons have the potential to synthesize dopamine, likely associated with a disproportional dopamine release within the striatum. We hypothesized that the serotonergic system is adaptively altered in the striatum due to the reduced dopaminergic input. To answer this question, we analyzed a transgenic rat PD model ubiquitously expressing human α-synuclein using a bacterial artificial chromosome. Neurite analysis showed a profound loss of dopaminergic fibers by 30–40% within the dorsal striatum paralleled by a 50% reduction of dopaminergic neurons in the substantia nigra pars compacta. In contrast, serotonergic fibers showed an increased fiber density in the dorsal striatum by 100%, while the number of serotonergic neurons within the raphe nuclei (RN) and its proximal neuritic processes were unaffected. Furthermore, both the dopaminergic and serotonergic fiber density remained unchanged in the neighboring motor cortex M1/M2. Interestingly, essential enzymes required for L-DOPA turnover and dopamine release were expressed in serotonergic neurons of the RN. In parallel, the serotonergic autoreceptor levels involved in a serotonergic negative feedback loop were reduced within the striatum, suggesting a dysfunctional neurotransmitter release. Overall, the increased serotonergic fiber density with its capacity for dopamine release within the striatum suggests a compensatory, site-specific serotonergic neuritogenesis. This maladaptive serotonergic plasticity may be linked to adverse symptoms such as LIDs in PD.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Dopamine; L-DOPA-induced dyskinesia; Parkinson's disease; Serotonin; Striatum; α-synuclein

Correction to: Gait variability as digital biomarker of disease severity in Huntington’s disease (Journal of Neurology, (2020), 10.1007/s00415-020-09725-3) - Gaßner, Heiko; Jensen, Dennis; Marxreiter, Franz; Kletsch, Anja; Bohlen, Stefan; Schubert, Robin; Muratori, Lisa M.; Eskofier, Björn; Klucken, Jochen; Winkler, Jürgen; Reilmann, Ralf; Kohl, Zacharias (Journal of Neurology, 2020)
The original version of this article unfortunately contained a mistake. The name of one author is not presented correctly in the author group. The correct name should be Franz Marxreiter.
CRIS-Team Scopus Importer:2020-04-03

Deep brain stimulation: Connectivity profile for bradykinesia alleviation - Strotzer, Quirin D.; Anthofer, Judith M.; Faltermeier, Rupert; Brawanski, Alexander T.; Torka, Elisabeth; Waldthaler, Josefine A.; Kohl, Zacharias; Fellner, Claudia; Beer, Anton L.; Schlaier, Juergen R. (Annals of Neurology, 2019)
Objective: Subthalamic deep brain stimulation may alleviate bradykinesia in Parkinson patients. Research suggests that this stimulation effect may be mediated by brain networks like the corticocerebellar loop. This study investigated the connectivity between stimulation sites and cortical and subcortical structures to identify connections for effective stimulation. Methods: We retrospectively investigated 21 patients with Parkinson disease with bilateral subthalamic deep brain stimulation. Stimulation effectiveness in reducing bradykinesia, tremor, and rigidity was evaluated for each electrode contact in brain hemispheres contralateral to the affected hemibody. Dysarthric side effects were also examined. Probabilistic tractography based on diffusion-weighted imaging was performed in individual patient-specific brains using electrode contacts as seeds. Connectivity profiles of contacts with effective and noneffective stimulation were compared. Results: Connectivity profiles of effective and noneffective contacts differed. Moreover, the connectivity profile for bradykinesia differed from that for rigidity, tremor, or dysarthria. Regarding bradykinesia, effective contacts were significantly more often connected with the ipsilateral superior cerebellar peduncle and the ipsilateral dentate nucleus, which correspond to the ipsilateral portion of the cerebellothalamocortical pathway. Rigidity was mitigated by stimulation of ascending brainstem and intralaminar thalamic connections. Tremor alleviation was related to connections with the internal capsule (anterior limb) and the pallidum. Dysarthric side effects were associated with connections to the supplementary motor area and the decussating cerebellothalamocortical pathway. Interpretation: Whereas bradykinesia seems to be mitigated by stimulation of the ascending, ipsilateral cerebellothalamocortical pathway, stimulation of the descending corticopontocerebellar pathway may be ineffective. Rigidity, tremor, and dysarthric side effects seem to be influenced by different neural networks. ANN NEUROL 2019.
CRIS-Team Scopus Importer:2019-05-17

Distinct Effects of Chronic Dopaminergic Stimulation on Hippocampal Neurogenesis and Striatal Doublecortin Expression in Adult Mice - Salvi, Rachele; Steigleder, Tobias; Schlachetzki, Johannes; Waldmann, Elisabeth; Schwab, Stefan; Winner, Beate; Winkler, Jürgen; Kohl, Zacharias (Frontiers in Neuroscience, 2016)
While adult neurogenesis is considered to be restricted to the hippocampal dentate gyrus (DG) and the subventricular zone (SVZ), recent studies in humans and rodents provide evidence for newly generated neurons in regions generally considered as non-neurogenic, e.g., the striatum. Stimulating dopaminergic neurotransmission has the potential to enhance adult neurogenesis in the SVZ and the DG most likely via D2/D3 dopamine (DA) receptors. Here, we investigated the effect of two distinct preferential D2/D3 DA agonists, Pramipexole (PPX), and Ropinirole (ROP), on adult neurogenesis in the hippocampus and striatum of adult naïve mice. To determine newly generated cells in the DG incorporating 5-bromo-2'-deoxyuridine (BrdU) a proliferation paradigm was performed in which two BrdU injections (100 mg/kg) were applied intraperitoneally within 12 h after a 14-days-DA agonist treatment. Interestingly, PPX, but not ROP significantly enhanced the proliferation in the DG by 42% compared to phosphate buffered saline (PBS)-injected control mice. To analyze the proportion of newly generated cells differentiating into mature neurons, we quantified cells co-expressing BrdU and Neuronal Nuclei (NeuN) 32 days after the last of five BrdU injections (50 mg/kg) applied at the beginning of 14-days DA agonist or PBS administration. Again, PPX only enhanced neurogenesis in the DG significantly compared to ROP- and PBS-injected mice. Moreover, we explored the pro-neurogenic effect of both DA agonists in the striatum by quantifying neuroblasts expressing doublecortin (DCX) in the entire striatum, as well as in the dorsal and ventral sub-regions separately. We observed a significantly higher number of DCX(+) neuroblasts in the dorsal compared to the ventral sub-region of the striatum in PPX-injected mice. These results suggest that the stimulation of hippocampal and dorsal striatal neurogenesis may be up-regulated by PPX. The increased generation of neural cells, both in constitutively active and quiescent neurogenic niches, might be related to the proportional higher D3 receptor affinity of PPX, non-dopaminergic effects of PPX, or altered motor behavior.
EVALuna2:5538

Distinct Pattern of Microgliosis in the Olfactory Bulb of Neurodegenerative Proteinopathies - Kohl, Zacharias; Schlachetzki, Johannes; Feldewerth, Judith; Hornauer, Philipp; Muench, Martina; Adame, Anthony; Riemenschneider, Markus J.; Winkler, Jürgen; Masliah, Eliezer (Neural Plasticity, 2017)
The olfactory bulb (OB) shows early neuropathological hallmarks in numerous neurodegenerative diseases, for example, in Alzheimer's disease (AD) and Parkinson's disease (PD). The glomerular and granular cell layer of the OB is characterized by preserved cellular plasticity in the adult brain. In turn, alterations of this cellular plasticity are related to neuroinflammation such as microglia activation, implicated in the pathogenesis of AD and PD, as well as frontotemporal lobe degeneration (FTLD). To determine microglia proliferation and activation we analyzed ionized calcium binding adaptor molecule 1 (Iba1) expressing microglia in the glomerular and granular cell layer, and the olfactory tract of the OB from patients with AD, PD dementia/dementia with Lewy bodies (PDD/DLB), and FTLD compared to age-matched controls. The number of Iba1 and CD68 positive microglia associated with enlarged amoeboid microglia was increased particularly in AD, to a lesser extent in FTLD and PDD/DLB as well, while the proportion of proliferating microglia was not altered. In addition, cells expressing the immature neuronal marker polysialylated neural cell adhesion molecule (PSA-NCAM) were increased in the glomerular layer of PDD/DLB and FTLD cases only. These findings provide novel and detailed insights into differential levels of microglia activation in the OB of neurodegenerative diseases.
EVALuna2:35932

Dysfunction of spatacsin leads to axonal pathology in SPG11-linked hereditary spastic paraplegia - Perez-Branguli, Francesc; Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Saul, Domenica; Rummel, Christine; Dorca-Arevalo, Jonatan; Regensburger, Martin; Graef, Daniela; Sock, Elisabeth; Blasi, Juan; et al. (Human Molecular Genetics, 2014)
Hereditary spastic paraplegias are a group of inherited motor neuron diseases characterized by progressive paraparesis and spasticity. Mutations in the spastic paraplegia gene SPG11, encoding spatacsin, cause an autosomal-recessive disease trait; however, the precise knowledge about the role of spatacsin in neurons is very limited. We for the first time analyzed the expression and function of spatacsin in human forebrain neurons derived from human pluripotent stem cells including lines from two SPG11 patients and two controls. SPG11 patients'-derived neurons exhibited downregulation of specific axonal-related genes, decreased neurite complexity and accumulation of membranous bodies within axonal processes. Altogether, these data point towards axonal pathologies in human neurons with SPG11 mutations. To further corroborate spatacsin function, we investigated human pluripotent stem cell-derived neurons and mouse cortical neurons. In these cells, spatacsin was located in axons and dendrites. It colocalized with cytoskeletal and synaptic vesicle (SV) markers and was present in synaptosomes. Knockdown of spatacsin in mouse cortical neurons evidenced that the loss of function of spatacsin leads to axonal instability by downregulation of acetylated tubulin. Finally, time-lapse assays performed in SPG11 patients'-derived neurons and spatacsin-silenced mouse neurons highlighted a reduction in the anterograde vesicle trafficking indicative of impaired axonal transport. By employing SPG11 patient-derived forebrain neurons and mouse cortical neurons, this study provides the first evidence that SPG11 is implicated in axonal maintenance and cargo trafficking. Understanding the cellular functions of spatacsin will allow deciphering mechanisms of motor cortex dysfunction in autosomal-recessive hereditary spastic paraplegia.
EVALuna2:4956

Early Degeneration of Both Dopaminergic and Serotonergic Axons - A Common Mechanism in Parkinson's Disease - Grosch, Janina; Winkler, Jürgen; Kohl, Zacharias (Frontiers in Cellular Neuroscience, 2016)
Motor symptoms in Parkinson's disease (PD) are tightly linked to the degeneration of substantia nigra dopaminergic neurons and their projections into the striatum. Moreover, a broad range of non-motor symptoms like anxiety and depression frequently occur in PD, most likely related to the loss of serotonergic neurons and their projections into corresponding target regions. Strikingly, nigral dopaminergic neurons and raphe serotonergic neurons are severely affected in PD showing characteristic hallmarks of PD neuropathology, in particular alpha-synuclein containing Lewy bodies and Lewy neurites. So far, the initial events underlying neurodegenerative processes in PD are not well understood. Several observations, however, indicate that neurites and synapses of diseased neurons may be the first subcellular compartments compromised by alpha-synuclein associated pathology. In particular axonal pathology and deficits in axonal transport may be leading to the onset of synucleinopathies such as PD. This review will highlight current findings derived from imaging and neuropathological studies in PD patients, as well as cellular and animal PD models, which define the initial underlying structural and molecular events within dopaminergic and serotonergic circuits leading to the 'dying back' degeneration of axonal projections in PD.
EVALuna2:33511

Fluoxetine rescues impaired hippocampal neurogenesis in a transgenic A53T synuclein mouse model. - Kohl, Zacharias; Winner, Beate; Ubhi, Kiren; Rockenstein, Edward; Mante, Michael; Muench, Martina; Barlow, Carolee; Carter, Todd; Masliah, Eliezer; Winkler, Jürgen (European Journal of Neuroscience, 2012)
The accumulation of alpha-synuclein in Lewy bodies and Lewy neurites of different neuronal populations is one of the neuropathological hallmarks in Parkinson disease (PD). Overexpression of human wildtype or mutant alpha-synuclein affects the generation of new neurons in the adult dentate gyrus (DG) of the hippocampus in models of PD. Hippocampal dysfunction with reduced neurogenesis plays an important role in the pathogenesis of depression, an important non-motor symptom in PD. Moreover, effective antidepressant treatment is still an unmet need in PD. The present study explored if impaired hippocampal neurogenesis in the A53T transgenic animal model of PD may be restored by chronic oral application of the selective serotonin reuptake inhibitor (SSRI) fluoxetine. First, we determined the expression pattern of transgenic mutant A53T synuclein in developing DG neurons and showed early expression of the transgene linked to a severely impaired neurogenesis. After chronic fluoxetine treatment we observed an increased adult neurogenesis in the hippocampus of more than threefold in treated A53T mice compared with controls. The pro-neurogenic effect of chronic fluoxetine application is predominantly related to an increased proliferation of neural precursor cells in the DG, and to a lesser extent by induction of differentiation into mature neurons. Analysis of the underlying mechanisms revealed an induction of brain-derived and glial cell-derived neurotrophic factor levels as a result of fluoxetine treatment. This study underlines the large potential of SSRI-dependent mechanisms to stimulate adult hippocampal neurogenesis in alpha-synuclein models and may lead to novel means to improve neuropsychiatric symptoms in PD.
EVALuna2:25298

Functional gait measures correlate to fear of falling, and quality of life in patients with Hereditary Spastic Paraplegia: A cross-sectional study - Gaßner, Heiko; List, Julia; Martindale, Christine; Regensburger, Martin; Klucken, Jochen; Winkler, Jürgen; Kohl, Zacharias (Clinical Neurology and Neurosurgery, 2021)
Objective: Gait impairment is the cardinal motor symptom in hereditary spastic paraplegias (HSPs) possibly linked to increased fear of falling and reduced quality of life (QoL). Disease specific symptoms in HSP are rated using the Spastic Paraplegia Rating Scale (SPRS). However, limited studies evaluated more objectively easy-to-apply gait measures by comparing these standardized assessments with patients’ self-perceived impairment and clinically established scores. Therefore, the aim of this study was to correlate functional gait measures with self-rating questionnaires for fear of falling and QoL, and with the SPRS as clinical gold standard. Methods: HSP patients (“pure” phenotype, n = 22) fulfilling the clinical diagnostic criteria for HSP and age-and gender-matched healthy subjects (n = 22) were included in this study. Motor impairment was evaluated using the SPRS, fear of falling by the Falls Efficacy Scale-International (FES-I), and QoL by SF-12. Functional gait measures included gait speed and step length (10-meter-walk-test), the Timed up and go test (TUG), and maximum walking distance (2-min-walking-test). Results: Functional gait measures correlated to fear of falling (gait speed: r = −0.726; step length: r = −0.689; TUG: r = 0.721; 2-min: r = −0.709) and the physical component of QoL (gait speed: r = 0.541; step length: r = 0.531; TUG: r = −0.512; 2-min: r = 0.548). Furthermore, FES-I (r = 0.767) and QoL (r = -0.728) correlated with the clinical gold standard (SPRS). Gait measures strongly correlated with SPRS (gait speed: r = −0.787; step length: r = −0.821; TUG: r = 0.756; 2-min: r = −0.791). Conclusion: Functional gait measures reflect fear of falling, QoL, and mobility in HSP. The metric, semi-quantitative gait measures complement the clinician's evaluation and support the clinical workup by more objective parameters.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Fear of falling; Gait analysis; Hereditary spastic paraplegia; Patient-reported outcome; Quality of life

Gait and cognition in Parkinson’s disease: cognitive impairment is inadequately reflected by gait performance during dual task - Gaßner, Heiko; Marxreiter, Franz; Steib, Simon; Kohl, Zacharias; Schlachetzki, Johannes; Adler, Werner; Eskofier, Björn; Pfeifer, Klaus; Winkler, Jürgen; Klucken, Jochen (Frontiers in Neurology, 2017)
Introduction: Cognitive and gait deficits are common symptoms in Parkinson's disease (PD). Motor-cognitive dual tasks (DTs) are used to explore the interplay between gait and cognition. However, it is unclear if DT gait performance is indicative for cognitive impairment. Therefore, the aim of this study was to investigate if cognitive deficits are reflected by DT costs of spatiotemporal gait parameters.Methods: Cognitive function, single task (ST) and DT gait performance were investigated in 67 PD patients. Cognition was assessed by the Montreal Cognitive Assessment (MoCA) followed by a standardized, sensor-based gait test and the identical gait test while subtracting serial 3's. Cognitive impairment was defined by a MoCA score <26. DT costs in gait parameters [(DT ST)/ST x 100] were calculated as a measure of DT effect on gait. Correlation analysis was used to evaluate the association between MoCA performance and gait parameters. In a linear regression model, DT gait costs and clinical confounders (age, gender, disease duration, motor impairment, medication, and depression) were correlated to cognitive performance. In a subgroup analysis, we compared matched groups of cognitively impaired and unimpaired PD patients regarding differences in ST, DT, and DT gait costs.Results: Correlation analysis revealed weak correlations between MoCA score and DT costs of gait parameters (r/r(Sp) <= 0.3). DT costs of stride length, swing time variability, and maximum toe clearance (vertical bar r/r(Sp)vertical bar > 0.2) were included in a regression analysis. The parameters only explain 8% of the cognitive variance. In combination with clinical confounders, regression analysis showed that these gait parameters explained 30% of MoCA performance. Group comparison revealed strong DT effects within both groups (large effect sizes), but significant between-group effects in DT gait costs were not observed.Conclusion: These findings suggest that DT gait performance is not indicative for cognitive impairment in PD. DT effects on gait parameters were substantial in cognitively impaired and unimpaired patients, thereby potentially overlaying the effect of cognitive impairment on DT gait costs. Limits of the MoCA in detecting motor-function specific cognitive performance or variable individual response to the DT as influencing factors cannot be excluded. Therefore, DT gait parameters as marker for cognitive performance should be carefully interpreted in the clinical context.
Keywords: Parkinson's disease; gait; cognition; dual task; gait analysis; Montreal Cognitive Assessment

Gait variability as digital biomarker of disease severity in Huntington’s disease - Gaßner, Heiko; Jensen, Dennis; Marxreiter, Franz; Kletsch, Anja; Bohlen, Stefan; Schubert, Robin; Muratori, Lisa M.; Eskofier, Björn; Klucken, Jochen; Winkler, Jürgen; Reilmann, Ralf; Kohl, Zacharias (Journal of Neurology, 2020)
Background Impaired gait plays an important role for quality of life in patients with Huntington's disease (HD). Measuring objective gait parameters in HD might provide an unbiased assessment of motor deficits in order to determine potential beneficial effects of future treatments. Objective To objectively identify characteristic features of gait in HD patients using sensor-based gait analysis. Particularly, gait parameters were correlated to the Unified Huntington's Disease Rating Scale, total motor score (TMS), and total functional capacity (TFC). Methods Patients with manifest HD at two German sites (n = 43) were included and clinically assessed during their annual ENROLL-HD visit. In addition, patients with HD and a cohort of age- and gender-matched controls performed a defined gait test (4 x 10 m walk). Gait patterns were recorded by inertial sensors attached to both shoes. Machine learning algorithms were applied to calculate spatio-temporal gait parameters and gait variability expressed as coefficient of variance (CV). Results Stride length (- 15%) and gait velocity (- 19%) were reduced, while stride (+ 7%) and stance time (+ 2%) were increased in patients with HD. However, parameters reflecting gait variability were substantially altered in HD patients (+ 17% stride length CV up to + 41% stride time CV with largest effect size) and showed strong correlations to TMS and TFC (0.416 <= r(Sp) <= 0.690). Objective gait variability parameters correlated with disease stage based upon TFC. Conclusions Sensor-based gait variability parameters were identified as clinically most relevant digital biomarker for gait impairment in HD. Altered gait variability represents characteristic irregularity of gait in HD and reflects disease severity.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Gait analysis; Gait variability; Huntington’s disease; Regularity of gait; Wearable sensors

Gastrointestinal microbiome in Parkinson's disease in a Bavarian cohort - Marxreiter, Franz; Cosma-Grigorov, Alexandra; Gaßner, Heiko; Meixner, Holger; Kohl, Zacharias; Neurath, Markus; Wirtz, Stefan; Winkler, Jürgen (2019)
EVALuna2:209001

Gene dosage-dependent rescue of HSP neurite defects in SPG4 patients' neurons - Havlicek, Steven; Kohl, Zacharias; Mishra, Himanshu Kumar; Prots, Iryna; Eberhardt, Esther; Denguir, Naime; Wend, Holger; Ploetz, Sonja; Boyer, Leah; Marchetto, Maria C. N.; Aigner, Stefan; Sticht, Heinrich; et al. (Human Molecular Genetics, 2014)
The hereditary spastic paraplegias (HSPs) are a heterogeneous group of motorneuron diseases characterized by progressive spasticity and paresis of the lower limbs. Mutations in Spastic Gait 4 (SPG4), encoding spastin, are the most frequent cause of HSP. To understand how mutations in SPG4 affect human neurons, we generated human induced pluripotent stem cells (hiPSCs) from fibroblasts of two patients carrying a c.1684C>T nonsense mutation and from two controls. These SPG4 and control hiPSCs were able to differentiate into neurons and glia at comparable efficiency. All known spastin isoforms were reduced in SPG4 neuronal cells. The complexity of SPG4 neurites was decreased, which was paralleled by an imbalance of axonal transport with less retrograde movement. Prominent neurite swellings with disrupted microtubules were present in SPG4 neurons at an ultrastructural level. While some of these swellings contain acetylated and detyrosinated tubulin, these tubulin modifications were unchanged in total cell lysates of SPG4 neurons. Upregulation of another microtubule-severing protein, p60 katanin, may partially compensate for microtubuli dynamics in SPG4 neurons. Overexpression of the M1 or M87 spastin isoforms restored neurite length, branching, numbers of primary neurites and reduced swellings in SPG4 neuronal cells. We conclude that neurite complexity and maintenance in HSP patient-derived neurons are critically sensitive to spastin gene dosage. Our data show that elevation of single spastin isoform levels is sufficient to restore neurite complexity and reduce neurite swellings in patient cells. Furthermore, our human model offers an ideal platform for pharmacological screenings with the goal to restore physiological spastin levels in SPG4 patients.
EVALuna2:2420

GSK3ss-Dependent Dysregulation of Neurodevelopment in SPG11-Patient Induced Pluripotent Stem Cell Model - Mishra, Himanshu Kumar; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Pérez-Brangulí, Francesc; Börstler, Tom; Anneser, Lukas; Minakaki, Georgia; Wend, Holger; Hampl, Martin; Leone, Marina; Brückner, Martina; et al. (Annals of Neurology, 2016)
Objective: Mutations in the spastic paraplegia gene 11 (SPG11), encoding spatacsin, cause the most frequent form of autosomal-recessive complex hereditary spastic paraplegia (HSP) and juvenile-onset amyotrophic lateral sclerosis (ALS5). When SPG11 is mutated, patients frequently present with spastic paraparesis, a thin corpus callosum, and cognitive impairment. We previously delineated a neurodegenerative phenotype in neurons of these patients. In the current study, we recapitulated early developmental phenotypes of SPG11 and outlined their cellular and molecular mechanisms in patient-specific induced pluripotent stem cell (iPSC)-derived cortical neural progenitor cells (NPCs).Methods: We generated and characterized iPSC-derived NPCs and neurons from 3 SPG11 patients and 2 age-matched controls.Results: Gene expression profiling of SPG11-NPCs revealed widespread transcriptional alterations in neurodevelopmental pathways. These include changes in cell-cycle, neurogenesis, cortical development pathways, in addition to autophagic deficits. More important, the GSK3ss-signaling pathway was found to be dysregulated in SPG11-NPCs. Impaired proliferation of SPG11-NPCs resulted in a significant diminution in the number of neural cells. The decrease in mitotically active SPG11-NPCs was rescued by GSK3 modulation.Interpretation: This iPSC-derived NPC model provides the first evidence for an early neurodevelopmental phenotype in SPG11, with GSK3ss as a potential novel target to reverse the disease phenotype.

Hereditary spastic paraplegia: Clinicogenetic lessons from 608 patients - Schuele, Rebecca; Wiethoff, Sarah; Martus, Peter; Karle, Kathrin N.; Otto, Susanne; Klebe, Stephan; Klimpe, Sven; Gallenmueller, Constanze; Kurzwelly, Delia; Henkel, Dorothea; Rimmele, Florian; Stolze, Henning; et al. (Annals of Neurology, 2016)
OBJECTIVE: Hereditary spastic paraplegias (HSPs) are genetically driven disorders with the hallmark of progressive spastic gait disturbance. To investigate the phenotypic spectrum, prognostic factors, and genotype-specific differences, we analyzed baseline data from a continuous, prospective cohort. METHODS: We recruited 608 HSP cases from 519 families of mostly German origin. Clinical severity was assessed by the Spastic Paraplegia Rating Scale. Complicating symptoms were recorded by a standardized inventory. RESULTS: Family history indicated dominant (43%), recessive (10%), and simplex (47%) disease. We observed a significant male predominance, particularly in simplex cases without a genetic diagnosis. Disease severity increased with disease duration. Earlier disease onset was associated with less severe disease. Specific complicating features including cognitive impairment, extrapyramidal or peripheral motor involvement, and ataxia were associated with worse disease severity. Disease severity also depended on the genotype. HSP cases maintained the ability to walk independently for a median disease duration of 22 years. Early onset cases were able to maintain free walking significantly longer and were at less risk to become wheelchair dependent. INTERPRETATION: This cross-sectional cohort study provides the first large-scale data on disease manifestation, progression, and modifying factors, with relevance for counseling of HSP families and planning of future cross-sectional and natural history studies. Later age of onset, specific complicating features, and the SPG11 genotype are strongly associated with more severe disease. Future interventional studies will require stratification for modifiers of disease progression identified in this study. Prospective longitudinal studies will verify progression rates calculated in this baseline analysis.
EVALuna2:33522

High-resolution diffusion tensor-imaging indicates asymmetric microstructural disorganization within substantia nigra in early Parkinson's disease - Knossalla, Frauke; Kohl, Zacharias; Winkler, Jürgen; Schwab, Stefan; Schenk, Thomas; Engelhorn, Tobias; Dörfler, Arnd; Gölitz, Philipp (Journal of Clinical Neuroscience, 2018)
BACKGROUND AND PURPOSE: Parkinson's disease (PD) is characterised by neuropathological degenerative changes in the substantia nigra (SN). Our study aimed to evaluate whether high-resolution diffusion tensor-imaging (DTI) can detect anatomical biomarkers in early-stage PD, and has the potential to visualize asymmetry effects comparable to the 123I-FP-CIT SPECT (DaTSCAN). METHODS: Ten early-stage PD patients with mild disease severity and ten age- and gender-matched healthy controls were examined with a high-resolution DTI protocol at a 3 Tesla MRI scanner to assess fractional anisotropy (FA) values in the ventral, middle and dorsal region of SN. In addition, a subgroup of 5 PD patients underwent a DaTSCAN. RESULTS: PD subjects showed reduced FA values in all SN regions compared to controls, but post hoc analysis revealed a significant reduction (p = .032) in the dorsal region. There was no significant correlation between clinical data and FA values. Subgroup analysis of PD patients with asymmetric radioligand uptake in the DaTSCAN demonstrated also significant asymmetric FA values (p = .027) in the dorsal region of SN. CONCLUSIONS: Our results provide preliminary evidence that high-resolution DTI can detect in early-stage PD patients with mild disease severity an anatomical biomarker in the dorsal region of SN, indicating microstructural disorganization. This biomarker, discriminating potentially in vivo between patients and healthy people, could be valuable for early PD diagnosis. If asymmetric radioligand uptake in the DaTSCAN was present, also asymmetry effects in the dorsal region of SN were obtained by DTI. These findings might contribute to improve effectiveness in diagnosing and monitoring PD.
EVALuna2:34272

Human SPG11 cerebral organoids reveal cortical neurogenesis impairment - Pérez-Brangulí, Francesc; Buchsbaum, Isabel; Pozner, Tatyana; Regensburger, Martin; Fan, Wenqiang; Schray, Annika; Börstler, Tom; Mishra, Himanshu Kumar; Gräf, Daniela; Kohl, Zacharias; Winkler, Jürgen; Berninger, Benedikt; et al. (Human Molecular Genetics, 2018)
SPG11 linked hereditary spastic paraplegia is a complex monogenic neurodegenerative disease that in addition to spastic paraplegia is characterized by childhood onset cognitive impairment, thin corpus callosum and enlarged ventricles. We have previously shown impaired proliferation of SPG11 neural progenitor cells (NPCs). For delineation of potential defect in SPG11 brain development we employ 2D culture systems and 3D human brain organoids derived from SPG11 patients' iPSC and controls. We reveal that an increased rate of asymmetric divisions of neural progenitor cells leads to proliferation defect, causing premature neurogenesis. Correspondingly, SPG11 organoids appeared smaller than controls and had larger ventricles as well as thinner germinal wall. Premature neurogenesis and organoid size were rescued by GSK3-inhibititors including the FDA-approved tideglusib. These findings shed light on the neurodevelopmental mechanisms underlying disease pathology.
EVALuna2:36370

Identification of symbol digit modality test score extremes in Huntington's disease - Braisch, Ulrike; Muche, Rainer; Rothenbacher, Dietrich; Landwehrmeyer, Georg Bernhard; Long, Jeffrey D.; Orth, Michael; Bachoud-Levi, Anne-Catherine; Bentivoglio, Anna-Rita; Biunno, Ida; Bonelli, Raphael M.; Burgunder, Jean-Marc; Dunnett, Stephen B.; et al. (American Journal of Medical Genetics Part B-Neuropsychiatric Genetics, 2019)
Studying individuals with extreme phenotypes could facilitate the understanding of disease modification by genetic or environmental factors. Our aim was to identify Huntington's disease (HD) patients with extreme symbol digit modality test (SDMT) scores. We first examined in HD the contribution of cognitive measures of the Unified Huntington's Disease Rating Scale (UHDRS) in predicting clinical endpoints. The language-independent SDMT was used to identify patients performing very well or very poorly relative to their CAG and age cohort. We used data from REGISTRY and COHORT observational study participants (5,603 HD participants with CAG repeats above 39 with 13,868 visits) and of 1,006 healthy volunteers (with 2,241 visits), included to identify natural aging and education effects on cognitive measures. Separate Cox proportional hazards models with CAG, age at study entry, education, sex, UHDRS total motor score and cognitive (SDMT, verbal fluency, Stroop tests) scores as covariates were used to predict clinical endpoints. Quantile regression for longitudinal language-independent SDMT data was used for boundary (2.5% and 97.5% quantiles) estimation and extreme score analyses stratified by age, education, and CAG repeat length. Ten percent of HD participants had an extreme SDMT phenotype for at least one visit. In contrast, only about 3% of participants were consistent SDMT extremes at two or more visits. The thresholds for the one-visit and two-visit extremes can be used to classify existing and new individuals. The identification of these phenotype extremes can be useful in the search for disease modifiers.
CRIS-Team WoS Importer:2019-03-29

Impaired adult olfactory bulb neurogenesis in the R6/2 mouse model of Huntington's disease - Winner, Beate; Kohl, Zacharias; Regensburger, Martin; Kandasamy, Mahesh; Winkler, Jürgen; et al. (BMC Neuroscience, 2010)
Background: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder linked to expanded CAG-triplet nucleotide repeats within the huntingtin gene. Intracellular huntingtin aggregates are present in neurons of distinct brain areas, among them regions of adult neurogenesis including the hippocampus and the subventricular zone/olfactory bulb system. Previously, reduced hippocampal neurogenesis has been detected in transgenic rodent models of HD. Therefore, we hypothesized that mutant huntingtin also affects newly generated neurons derived from the subventricular zone of adult R6/2 HD mice.Results: We observed a redirection of immature neuroblasts towards the striatum, however failed to detect new mature neurons. We further analyzed adult neurogenesis in the granular cell layer and the glomerular layer of the olfactory bulb, the physiological target region of subventricular zone-derived neuroblasts. Using bromodeoxyuridine to label proliferating cells, we observed in both neurogenic regions of the olfactory bulb a reduction in newly generated neurons.Conclusion: These findings suggest that the striatal environment, severely affected in R6/2 mice, is capable of attracting neuroblasts, however this region fails to provide sufficient signals for neuronal maturation. Moreover, in transgenic R6/2 animals, the hostile huntingtin-associated microenvironment in the olfactory bulb interferes with the survival and integration of new mature neurons. Taken together, endogenous cell repair strategies in HD may require additional factors for the differentiation and survival of newly generated neurons both in neurogenic and non-neurogenic regions.

Inertial Gait Sensors to Measure Mobility and Functioning in Hereditary Spastic Paraplegia A Cross-sectional Multicenter Clinical Study - Regensburger, Martin; Spatz, Imke; Ollenschläger, Malte; Martindale, Christine; Lindeburg, Philipp; Kohl, Zacharias; Eskofier, Björn; Klucken, Jochen; Schuele, Rebecca; Klebe, Stephan; Winkler, Jürgen; Gaßner, Heiko (Neurology, 2022)
Background and Objectives Hereditary spastic paraplegia (HSP) causes progressive spasticity and weakness of the lower limbs. As neurologic examination and the clinical Spastic Paraplegia Rating Scale (SPRS) are subject to potential patient-dependent and clinician-dependent bias, instrumented gait analysis bears the potential to objectively quantify impaired gait. The aim of this study was to investigate gait cyclicity parameters by application of a mobile gait analysis system in a cross-sectional cohort of patients with HSP and a longitudinal fast progressing subcohort. Methods Using wearable sensors attached to the shoes, patients with HSP and controls performed a 4 x 10 m walking test during regular visits in 3 outpatient centers. Patients were also rated according to the SPRS, and in a subset, questionnaires on quality of life and fear of falling were obtained. An unsupervised segmentation algorithm was used to extract stride parameters and respective coefficients of variation. Results Mobile gait analysis was performed in a total of 112 ambulatory patients with HSP and 112 age-matched and sex-matched controls. Although swing time was unchanged compared with controls, there were significant increases in the duration of the total stride phase and the duration of the stance phase, both regarding absolute values and coefficients of variation values. Although stride parameters did not correlate with age, weight, or height of the patients, there were significant associations of absolute stride parameters with single SPRS items reflecting impaired mobility (|r| > 0.50), with patients' quality of life (|r| > 0.44), and notably with disease duration (|r| > 0.27). Sensor-derived coefficients of variation, on the other hand, were associated with patient-reported fear of falling (|r| > 0.41) and cognitive impairment (|r| > 0.40). In a small 1-year follow-up analysis of patients with complicated HSP and fast progression, the absolute values of mobile gait parameters had significantly worsened compared with baseline. Discussion The presented wearable sensor system provides parameters of stride characteristics which seem clinically valid to reflect gait impairment in HSP. Owing to the feasibility regarding time, space, and costs, this study forms the basis for larger scale longitudinal and interventional studies in HSP.
CRIS-Team WoS Importer:2022-09-23

Intracellular A53T Mutant alpha-Synuclein Impairs Adult Hippocampal Newborn Neuron Integration - Winner, Beate; Regensburger, Martin; Stemick, Judith; Masliah, Eliezer; Kohl, Zacharias (Frontiers in Cell and Developmental Biology, 2020)
Dendritic dysfunction is an early event in alpha-synuclein (alpha-syn) mediated neurodegeneration. Altered postsynaptic potential and loss of dendritic spines have been observed in different in vitro and in vivo models of synucleinopathies. The integration of newborn neurons into the hippocampus offers the possibility to study dendrite and spine formation in an adult environment. Specifically, survival of hippocampal adult newborn neurons is regulated by synaptic input and was reduced in a mouse model transgenic for human A53T mutant alpha-syn. We thus hypothesized that dendritic integration of newborn neurons is impaired in the adult hippocampus of A53T mice. We analyzed dendritic morphology of adult hippocampal neurons 1 month after retroviral labeling. Dendrite length was unchanged in the dentate gyrus of A53T transgenic mice. However, spine density and mushroom spine density of newborn neurons were severely decreased. In this mouse model, transgenic alpha-syn was expressed both within newborn neurons and within their environment. To specifically determine the cell autonomous effects, we analyzed cell-intrinsic overexpression of A53T alpha-syn using a retrovirus. Since A53T alpha-syn overexpressing newborn neurons exhibited decreased spine density 1 month after labeling, we conclude that cell-intrinsic A53T alpha-syn impairs postsynaptic integration of adult hippocampal newborn neurons. Our findings further support the role of postsynaptic degeneration as an early feature in synucleinopathies and provide a model system to study underlying mechanisms.
Keywords: A53T alpha-synuclein; cell autonomous; adult neurogenesis; hippocampus; spines

Intracellular A53T Mutant α-Synuclein Impairs Adult Hippocampal Newborn Neuron Integration - Regensburger, Martin; Stemick, Judith; Masliah, Eliezer; Kohl, Zacharias; Winner, Beate (Frontiers in Cell and Developmental Biology, 2020)
Dendritic dysfunction is an early event in α-synuclein (α-syn) mediated neurodegeneration. Altered postsynaptic potential and loss of dendritic spines have been observed in different in vitro and in vivo models of synucleinopathies. The integration of newborn neurons into the hippocampus offers the possibility to study dendrite and spine formation in an adult environment. Specifically, survival of hippocampal adult newborn neurons is regulated by synaptic input and was reduced in a mouse model transgenic for human A53T mutant α-syn. We thus hypothesized that dendritic integration of newborn neurons is impaired in the adult hippocampus of A53T mice. We analyzed dendritic morphology of adult hippocampal neurons 1 month after retroviral labeling. Dendrite length was unchanged in the dentate gyrus of A53T transgenic mice. However, spine density and mushroom spine density of newborn neurons were severely decreased. In this mouse model, transgenic α-syn was expressed both within newborn neurons and within their environment. To specifically determine the cell autonomous effects, we analyzed cell-intrinsic overexpression of A53T α-syn using a retrovirus. Since A53T α-syn overexpressing newborn neurons exhibited decreased spine density 1 month after labeling, we conclude that cell-intrinsic A53T α-syn impairs postsynaptic integration of adult hippocampal newborn neurons. Our findings further support the role of postsynaptic degeneration as an early feature in synucleinopathies and provide a model system to study underlying mechanisms.
CRIS-Team Scopus Importer:2020-12-04
Keywords: A53T alpha-synuclein; adult neurogenesis; cell autonomous; hippocampus; spines

Involvement of obliquus capitis inferior muscle in dystonic head tremor - Schramm, Axel; Huber, D.; Möbius, Cornelia; Muenchau, A.; Kohl, Zacharias; Baeumer, T. (Parkinsonism & Related Disorders, 2017)
Head tremor is a common feature in cervical dystonia (CD) and often less responsive to botulinum neurotoxin (BoNT) treatment than dystonic posturing. Ultrasound allows accurate targeting of deeper neck muscles.In 35 CD patients with dystonic head tremor the depth and thickness of the splenius capitis (SPL), semispinalis capitis and obliquus capitis inferior muscles (OCI) were assessed using ultrasound. Ultrasound guided EMG recordings were performed from the SPL and OCI.Burst-like tremor activity was present in both OCI in 25 and in one in 10 patients. In 18 patients, tremor activity was present in one SPL and in 2 in both SPL. Depth and thickness of OCI, SPL and semispinalis capitis muscles were very variable.Muscular activity underlying tremulous CD is most commonly present in OCI. Due to the variability of muscle thickness, we suggest ultrasound guided BoNT injections into OCI.
EVALuna2:22566

Layer-specific axonal degeneration of serotonergic fibers in the prefrontal cortex of aged A53T α-synuclein–expressing mice - Wihan, Jeanette; Grosch, Janina; Kalinichenko, Liubov; Müller, Christian P.; Winkler, Jürgen; Kohl, Zacharias (Neurobiology of Aging, 2019)
Axonal pathology precedes dopaminergic cell loss in Parkinson's disease (PD), indicating a dying back axonopathy of nigrostriatal projections. Although most attention focused on the dopaminergic system, increasing evidence implies a compromised serotonergic system in PD as well. By combining immunohistological and biochemical approaches, a profound layer-specific reduction of the serotonergic input to the prefrontal cortex (PFC)layers II and V/VI in aged mutant A53T α-synuclein–expressing mice (A53T mice)was detected. In addition, the altered fiber network was characterized by swollen axons and enlarged axonal varicosities within all PFC layers, but most pronounced in PFC layer I. Although prefrontal serotonin levels and synaptic protein expression were preserved, aged A53T mice showed increased levels of kinesin family member 1a and vesicular monoamine transporter 2. Together with increased tryptophan hydroxylase 2 mRNA levels in the raphe nuclei and an elevated serotonin receptor 1b expression in the PFC, these findings point to compensatory mechanisms within the serotonergic system to overcome the reduced neuritic input to the PFC in this transgenic animal model for PD.
CRIS-Team Scopus Importer:2019-05-16
Keywords: Alpha-synuclein; Parkinson's disease; Prefrontal cortex; Serotonin; Serotonin transporter

Mechanistic basis of an epistatic interaction reducing age at onset in hereditary spastic paraplegia - Newton, Timothy; Allison, Rachel; Edgar, James R.; Lumb, Jennifer H.; Rodger, Catherine E.; Manna, Paul T.; Rizo, Tania; Kohl, Zacharias; Nygren, Anders O. H.; Arning, Larissa; Schuele, Rebecca; Depienne, Christel; et al. (Brain, 2018)
Many genetic neurological disorders exhibit variable expression within affected families, often exemplified by variations in disease age at onset. Epistatic effects (i.e. effects of modifier genes on the disease gene) may underlie this variation, but the mechanistic basis for such epistatic interactions is rarely understood. Here we report a novel epistatic interaction between SPAST and the contiguous gene DPY30, which modifies age at onset in hereditary spastic paraplegia, a genetic axonopathy. We found that patients with hereditary spastic paraplegia caused by genomic deletions of SPAST that extended into DPY30 had a significantly younger age at onset. We show that, like spastin, the protein encoded by SPAST, the DPY30 protein controls endosomal tubule fission, traffic of mannose 6-phosphate receptors from endosomes to the Golgi, and lysosomal ultrastructural morphology. We propose that additive effects on this pathway explain the reduced age at onset of hereditary spastic paraplegia in patients who are haploinsufficient for both genes.
EVALuna2:35784

Mobile Gait Analysis Using Personalised Hidden Markov Models for Hereditary Spastic Paraplegia Patients - Martindale, Christine; Roth, Nils; Gaßner, Heiko; Jensen, Dennis; Kohl, Zacharias; Eskofier, Björn (2018 40th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2018)
Gait analysis provides a quantitative method to assess disease progression or intervention effect on gait disorders. While mobile gait analysis enables continuous monitoring in free living conditions, state of the art gait analysis for diseases such as hereditary spastic paraplegia (HSP) is currently limited to motion capture systems which are large and expensive. The challenge with HSP is its heterogeneous nature and rarity, leading to a wide range of ages, severity and gait patterns as well as small patient numbers. We propose a sensor-based mobile solution, based on a personalised hierarchical hidden Markov Model (hHMM) to extract spatio-temporal gait parameters. This personalised hHMM achieves a mean absolute error of 0.04 s pm 0.03 s for stride time estimation with respect to a GAITRite® reference system. We use the successful extraction of initial ground contact to explore the limits of the double integration method for such heterogeneous diseases. While our personalised model compensates for the heterogeneity of the disease, it would require a new model per patient. We observed that the general model was sufficient for some of the less severely affected patient

Motor neuron diseases. Clinical and genetic differential diagnostics - Regensburger, Martin; Weidner, N.; Kohl, Zacharias (Der Nervenarzt, 2018)
The causes of degenerative disease of the upper and lower motor neurons are incompletely understood. In this review the current concepts in the clinical and genetic differential diagnostics of motor neuron diseases are presented. Hereditary spastic paraplegia, primary lateral sclerosis, spinal muscular atrophy and amyotrophic lateral sclerosis are explained, structured according to the affection of the upper and/or lower motor neuron. The substantial variability in the presentation and course of motor neuron diseases as well as the lack of specific laboratory tests hinder an early diagnosis. The precise description of the clinical picture, thorough testing of possible differential diagnoses as well as monitoring of the clinical course are essential. Genetic analyses should be offered to patients with a positive family history. Early identification of clinical and genetic subentities of the individual motor neuron diseases is a prerequisite for future neuroprotective interventions.
EVALuna2:35783

Need for high-resolution Genetic Analysis in iPSC: Results and Lessons from the ForIPS Consortium - Popp, Bernt; Krumbiegel, Mandy; Grosch, Janina; Sommer, Annika; Uebe, Steffen; Kohl, Zacharias; Ploetz, Sonja; Farrell, Michaela; Trautmann, Udo; Kraus, Cornelia; Ekici, Arif Bülent; Asadollahi, Reza; et al. (Scientific Reports, 2018)
Genetic integrity of induced pluripotent stem cells (iPSCs) is essential for their validity as disease models and for potential therapeutic use. We describe the comprehensive analysis in the ForIPS consortium: an iPSC collection from donors with neurological diseases and healthy controls. Characterization included pluripotency confirmation, fingerprinting, conventional and molecular karyotyping in all lines. In the majority, somatic copy number variants (CNVs) were identified. A subset with available matched donor DNA was selected for comparative exome sequencing. We identified single nucleotide variants (SNVs) at different allelic frequencies in each clone with high variability in mutational load. Low frequencies of variants in parental fibroblasts highlight the importance of germline samples. Somatic variant number was independent from reprogramming, cell type and passage. Comparison with disease genes and prediction scores suggest biological relevance for some variants. We show that high-throughput sequencing has value beyond SNV detection and the requirement to individually evaluate each clone.
EVALuna2:34839

Neurodegenerative disease and adult neurogenesis - Winner, Beate; Kohl, Zacharias; et al. (European Journal of Neuroscience, 2011)
Keywords: Parkinson's disease; Adult neural progenitor cells; Dentate gyrus; Alzheimer's disease; Olfactory bulb; Huntington's disease

Neurometabolic Dysfunction in SPG11 Hereditary Spastic Paraplegia. - Winner, Beate; Marterstock, Dominique; Kopp, Christoph; Dörfler, Arnd; Regensburger, Martin; Krumm, Laura; Schmidt, Manuel; Schmid, Andreas; Spatz, Imke; Marterstock, Dominique; Kopp, Christoph; Kohl, Zacharias; et al. (Nutrients, 2022)
Body composition, adipokine levels, and hypothalamic volume are altered in SPG11. Our data indicate a link between obesity and hypothalamic neurodegeneration in SPG11 and imply that specific metabolic interventions may prevent obesity despite severely impaired mobility in SPG11. Pathogenic variants in SPG11 cause the most common autosomal recessive complicated hereditary spastic paraplegia. Besides the prototypical combination of spastic paraplegia with a thin corpus callosum, obesity has increasingly been reported in this multisystem neurodegenerative disease. However, a detailed analysis of the metabolic state is lacking. In order to characterize metabolic alterations, a cross-sectional analysis was performed comparing SPG11 patients (n = 16) and matched healthy controls (n = 16). We quantified anthropometric parameters, body composition as determined by bioimpedance spectroscopy, and serum metabolic biomarkers, and we measured hypothalamic volume by high-field MRI. Compared to healthy controls, SPG11 patients exhibited profound changes in body composition, characterized by increased fat tissue index, decreased lean tissue index, and decreased muscle mass. The presence of lymphedema correlated with increased extracellular fluid. The serum levels of the adipokines leptin, resistin, and progranulin were significantly altered in SPG11 while adiponectin and C1q/TNF-related protein 3 (CTRP-3) were unchanged. MRI volumetry revealed a decreased hypothalamic volume in SPG11 patients. CONCLUSIONS BACKGROUND METHODS RESULTS
Keywords: SPG11; adipokines; bioimpedance spectroscopy; hypothalamus; leptin; obesity

Neuropsychology and MRI correlates of neurodegeneration in SPG11 hereditary spastic paraplegia - Utz, Kathrin; Kohl, Zacharias; Marterstock, Dominique; Dörfler, Arnd; Winkler, Jürgen; Schmidt, Manuel; Regensburger, Martin (Orphanet Journal of Rare Diseases, 2022)
Background: SPG11-linked hereditary spastic paraplegia is characterized by multisystem neurodegeneration leading to a complex clinical and yet incurable phenotype of progressive spasticity and weakness. Severe cognitive symptoms are present in the majority of SPG11 patients, but a systematic and multidimensional analysis of the neuropsychological phenotype in a larger cohort is lacking. While thinning of the corpus callosum is a well-known structural hallmark observed in SPG11 patients, the neuroanatomical pattern of cortical degeneration is less understood. We here aimed to integrate neuropsychological and brain morphometric measures in SPG11. Methods: We examined the neuropsychological profile in 16 SPG11 patients using a defined neuropsychological testing battery. Long-term follow up testing was performed in 7 patients. Cortical and subcortical degeneration was analyzed using an approved, artificial intelligence based magnetic resonance imaging brain morphometry, comparing patients to established reference values and to matched controls. Results: In SPG11 patients, verbal fluency and memory as well as frontal-executive functions were severely impaired. Later disease stages were associated with a global pattern of impairments. Interestingly, reaction times correlated significantly with disease progression. Brain morphometry showed a significant reduction of cortical and subcortical parenchymal volume following a rostro-caudal gradient in SPG11. Whereas performance in memory tasks correlated with white matter damage, verbal fluency measures showed strong associations with frontal and parietal cortical volumes. Conclusions: The present data will help define neuropsychological and imaging read out parameters in early as well as in advanced clinical stages for future interventional trials in SPG11.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Brain morphometry; Neuropsychology; Spastic paraplegia; SPG11; Verbal fluency

Novel Biallelic CTSD Gene Variants Cause Late-Onset Ataxia and Retinitis Pigmentosa - Regensburger, Martin; Minakaki, Georgia; Kettwig, Matthias; Huchzermeyer, Cord; Eisenhut, Felix; Haack, Tobias B.; Kohl, Zacharias; Winkler, Jürgen (Movement Disorders, 2020)
CRIS-Team Scopus Importer:2020-05-29

Pain relief in a neuropathy patient by lacosamide: Proof of principle of clinical translation from patient-specific iPS cell-derived nociceptors - Namer, Barbara; Schmidt, Diana; Eberhardt, Esther; Maroni, Michele; Dorfmeister, Eva; Kleggetveit, Inge Petter; Kaluza, Luisa; Meents, Jannis; Gerlach, Aaron; Lin, Zhixin; Winterpacht, Andreas; Dragicevic, Elena; et al. (EBioMedicine, 2018)
BACKGROUND: Small fiber neuropathy (SFN) is a severe and disabling chronic pain syndrome with no causal and limited symptomatic treatment options. Mechanistically based individual treatment is not available. We report an in-vitro predicted individualized treatment success in one therapy-refractory Caucasian patient suffering from SFN for over ten years. METHODS: Intrinsic excitability of human induced pluripotent stem cell (iPSC) derived nociceptors from this patient and respective controls were recorded on multi-electrode (MEA) arrays, in the presence and absence of lacosamide. The patient's pain ratings were assessed by a visual analogue scale (10: worst pain, 0: no pain) and treatment effect was objectified by microneurography recordings of the patient's single nerve C-fibers. FINDINGS: We identified patient-specific changes in iPSC-derived nociceptor excitability in MEA recordings, which were reverted by the FDA-approved compound lacosamide in vitro. Using this drug for individualized treatment of this patient, the patient's pain ratings decreased from 7.5 to 1.5. Consistent with the pain relief reported by the patient, microneurography recordings of the patient's single nerve fibers mirrored a reduced spontaneous nociceptor (C-fiber) activity in the patient during lacosamide treatment. Microneurography recordings yielded an objective measurement of altered peripheral nociceptor activity following treatment. INTERPRETATION: Thus, we are here presenting one example of successful patient specific precision medicine using iPSC technology and individualized therapeutic treatment based on patient-derived sensory neurons.
EVALuna2:35119

Paradoxical kinesia in Parkinson's disease revisited: Anticipation of temporal constraints is critical - Distler, Michael; Schlachetzki, Johannes; Kohl, Zacharias; Winkler, Jürgen; Schenk, Thomas (Neuropsychologia, 2016)
Slowness of movement, called bradykinesia is the cardinal symptom of Parkinson's disease. Under distinct but not yet well-defined circumstances, patients with Parkinson's disease are able to overcome bradykinesia. One common hypothesis for this phenomenon termed paradoxical kinesia in Parkinson's disease postulates that the presentation of external sensory triggers is pivotal to elicit significant increase of motor velocity. In the present study, we examined an alternative hypothesis, namely that an internal cue in the absence of sensory cues are linked to paradoxical kinesia. To test this alternative hypothesis, patients with Parkinson's disease and healthy age-matched controls (n=9 per group) performed two movement tasks. In the stationary-object prehension task, subjects had to pick up a stationary target object. For the escaping-object task, the participants had to pick up the target object before it moved out of reach. The time available to reach for the object was adjusted individually to ensure comparable difficulty across participants. Reaction time, movement duration, and maximum velocity were assessed for both movement tasks. In Parkinson's disease patients and healthy controls, anticipation of the imminent movement of a target object significantly decreased reaction time, movement duration, and increased maximum movement velocity. The increase of maximum movement velocity in the escape-condition was significantly more pronounced for Parkinson's disease patients as compared to healthy controls. We provide evidence that internal cues such as temporal constraints are sufficient to diminish the cardinal clinical symptom of bradykinesia in Parkinson's disease. Our results suggest that expectations rather than sensory cues are critical for the emergence of paradoxical kinesia and we discuss the implications of our findings for an account of paradoxical kinesia.
EVALuna2:33521

Pattern of Functional TTX-Resistant Sodium Channels Reveals a Developmental Stage of Human iPSC- and ESC-Derived Nociceptors - Eberhardt, Esther; Havlicek, Steven; Schmidt, Diana; Link, Andrea; Neacsu, Cristian; Kohl, Zacharias; Hampl, Martin; Kist, Andreas; Klinger, Alexandra; Nau, Carla; Schüttler, Jürgen; Alzheimer, Christian; et al. (Stem Cell Reports, 2015)
Human pluripotent stem cells (hPSCs) offer the opportunity to generate neuronal cells, including nociceptors. Using a chemical-based approach, we generated nociceptive sensory neurons from HUES6 embryonic stem cells and retrovirally reprogrammed induced hPSCs derived from fibroblasts. The nociceptive neurons expressed respective markers and showed tetrodotoxin-sensitive (TTXs) and -resistant (TTXr) voltage-gated sodium currents in patch-clamp experiments. In contrast to their counterparts from rodent dorsal root ganglia, TTXr currents of hPSC-derived nociceptors unexpectedly displayed a significantly more hyperpolarized voltage dependence of activation and fast inactivation. This apparent discrepancy is most likely due to a substantial expression of the developmentally important sodium channel NAV1.5. In view of the obstacles to recapitulate neuropathic pain in animal models, our data advance hPSC-derived nociceptors as a better model to study developmental and pathogenetic processes in human nociceptive neurons and to develop more specific small molecules to attenuate pain.
EVALuna2:2465

Segmentation of gait sequences using inertial sensor data in hereditary spastic paraplegia - Martindale, Christine; Strauss, Martin; Gaßner, Heiko; List, Julia; Müller, Meinard; Klucken, Jochen; Kohl, Zacharias; Eskofier, Björn (Engineering in Medicine and Biology Society (EMBC), 2017 39th Annual International Conference of the IEEE, 2017)
Gait analysis is an important tool for diagnosis, monitoring and treatment of neurological diseases. Among these are hereditary spastic paraplegias (HSPs) whose main characteristic is heterogeneous gait disturbance. So far HSP gait has been analysed in a limited number of studies, and within a laboratory set up only. Although the rarity of orphan diseases often limits larger scale studies, the investigation of these diseases is still important, not only to the affect population, but also for other diseases which share gait characteristics. In this paper we use foot-mounted inertial measurement units (IMU) as a mobile solution to measure the gait of 21 HSP patients while performing a 4 by 10 m walk at self-selected pace. Two algorithms common to other gait analysis solutions, the hidden Markov model (HMM) and dynamic time warping (DTW), were applied to these signals in order to investigate their effectiveness when faced with the heterogeneous nature and range of foot strike techniques of HSP gait, sometimes even lacking a heel strike. Using a nested cross validation for parameter choice and validation, the HMM was found to be superior for segmentation purposes with a mean segmentation error of 0.10 ± 0.05 s. Stride segmentation of such a diverse dataset is the first step towards creating a clinically relevant system which could assist physicians working with HSP patients by providing objective, automated gait parameters. To the best of the authors’ knowledge, this is the first paper to investigate solutions for mobile gait analysis of patients affected by HSPs. Ultimately, automated, mobile gait analysis of HSP patients would allow ongoing and long term monitoring, providing useful insights into this orphan diseas
Keywords: Hidden Markov models; segmentation; gait analysis; hereditary spastic paraplegia

Sensor-based gait analysis distinguishes fallers from non-fallers in Parkinson's disease under clinical and real-life conditions - Gladow, Till; Gaßner, Heiko; Ullrich, Martin; Hannink, Julius; Roth, Nils; Marxreiter, Franz; Küderle, Arne; Kohl, Zacharias; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen (2019)
EVALuna2:213285

Sensor-based gait analysis of individualized improvement during apomorphine titration in Parkinson's disease - Marxreiter, Franz; Gaßner, Heiko; Borozdina, Olga; Barth, Jens; Kohl, Zacharias; Schlachetzki, Johannes; Thun-Hohenstein, Caroline; Volc, Dieter; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen (Journal of Neurology, 2018)
Mobile, sensor-based gait analysis in Parkinson's disease (PD) facilitates the objective measurement of gait parameters in cross-sectional studies. Besides becoming outcome measures for clinical studies, the application of gait parameters in personalized clinical decision support is limited. Therefore, the aim of this study was to evaluate whether the individual response of PD patients to dopaminergic treatment may be measured by sensor-based gait analysis. 13 PD patients received apomorphine every 15 min to incrementally increase the bioavailable apomorphine dose. Motor performance (UPDRS III) was assessed 10 min after each apomorphine injection. Gait parameters were obtained after each UPDRS III rating from a 2 × 10 m gait sequence, providing 41.2 ± 9.2 strides per patient and injection. Gait parameters and UPDRS III ratings were compared cross-sectionally after apomorphine titration, and more importantly between consecutive injections for each patient individually. For the individual response, the effect size Cohen's d for gait parameter changes was calculated based on the stride variations of each gait sequence after each injection. Cross-sectionally, apomorphine improved stride speed, length, gait velocity, maximum toe clearance, and toe off angle. Between injections, the effect size for individual changes in stride speed, length, and maximum toe clearance correlated to the motor improvement in each patient. In addition, significant changes of stride length between injections were significantly associated with UPDRS III improvements. We therefore show, that sensor-based gait analysis provides objective gait parameters that support clinical assessment of individual PD patients during dopaminergic treatment. We propose clinically relevant instrumented gait parameters for treatment studies and especially clinical care.
EVALuna2:36376
Keywords: Parkinson’s disease; Sensor-based gait analysis; Apomorphine; Gait parameter; Precision medicine

Serotonergic dysfunction in the A53T alpha-synuclein mouse model of Parkinson's disease - Deußer, Janina; Schmidt, Stefanie; Ettle, Benjamin; Ploetz, Sonja; Huber, Sabine; Müller, Christiane; Masliah, Eliezer; Winkler, Jürgen; Kohl, Zacharias (Journal of Neurochemistry, 2015)
Parkinson's disease, neuropathologically defined by the aggregation of ?-synuclein, is characterized by neuropsychiatric symptoms such as depression and anxiety preceding the onset of motor symptoms. A loss of serotonergic neurons or their projections into the hippocampus and alterations in serotonin release may be linked to these symptoms. Here, we investigate the effect of human A53T ?-synuclein on serotonergic neurons using 12-months-old transgenic mice. We detected human ?-synuclein in the perikarya of brainstem median and dorsal raphe neurons as well as in serotonergic fibers in the hippocampus. Despite intracellular ?-synuclein accumulation there was no loss of serotonergic neurons in dorsal and median raphe nuclei of A53T ?-synuclein mice. However, serotonin levels were significantly reduced in the brainstem. In addition, serotonergic fiber density in the dorsal dentate gyrus was significantly less dense in transgenic mice. Interestingly, we detected a significantly compromised increase in doublecortin+ neuroblasts after chronic treatment with fluoxetine at the site of reduced serotonergic innervation, the infrapyramidal blade of the dorsal dentate gyrus in A53T ?-synuclein mice. This suggests that ?-synuclein affects serotonergic projections in a spatially distinct pattern within the hippocampus thereby influencing the response to antidepressant treatment.
EVALuna2:23680

Serotonin in Parkinson's disease - Kohl, Zacharias; Winkler, Jürgen (Handbook of Behavioral Neuroscience, 2020)
Motor symptoms in Parkinson's disease (PD) are tightly linked to the degeneration of substantia nigra dopaminergic neurons and their projections into the striatum leading to the prototypical motor manifestations of the disease. However, the affection of various other neurotransmitters accounts for a large variety of motor as well as nonmotor symptoms in PD. The loss of serotonergic neurons and alterations of their projections into corresponding targets play an important role in a broad range of motor as well as nonmotor symptoms, including tremor, fluctuations of motor function, cognition, depression, anxiety, and psychosis. Here, we highlight current findings from neuropathological studies as well as animal models of PD, and relate them to recent clinical imaging results, underlining the importance of a compromised serotonergic system in PD and address potential future treatment strategies.
CRIS-Team Scopus Importer:2020-01-31
Keywords: 5-HT; Alpha-synuclein; Hippocampus; Hyperinnervation; Parkinson's disease; Serotonin receptor; Striatum; Synaptic loss

Severely impaired hippocampal neurogenesis associates with an early serotonergic deficit in a BAC ?-synuclein transgenic rat model of Parkinson's disease - Kohl, Zacharias; Ben Abdallah, Nada; Vogelgsang, Jonathan; Tischer, Lucas; Deußer, Janina; Amato, Davide; Anderson, Scott; Müller, Christian P.; Riess, Olaf; Masliah, Eliezer; Nuber, Silke; Winkler, Jürgen (Neurobiology of Disease, 2016)
Parkinson's disease (PD) is a multisystem disorder, involving several monoaminergic neurotransmitter systems resulting in a broad range of motor and non-motor symptoms. Pathological hallmarks of PD are the loss of dopaminergic neurons and the accumulation of alpha-synuclein, however also being present in the serotonergic raphe nuclei early in the disease course. The dysfunction of the serotonergic system projecting to the hippocampus may contribute to early non-motor symptoms such as anxiety and depression. The adult hippocampal dentate gyrus (DG), a unique niche of the forebrain continuously generating new neurons, may particularly present enhanced susceptibility towards accumulating alpha-synuclein levels. The underlying molecular mechanisms in the context of neuronal maturation and survival of new-born neurons are yet not well understood. To characterize the effects of overexpression of human full-length alpha-synuclein on hippocampal cellular and synaptic plasticity, we used a recently generated BAC alpha-synuclein transgenic rat model showing important features of PD such as widespread and progressive alpha-synuclein aggregation pathology, dopamine loss and age-dependent motor decline. At the age of four months, thus prior to the occurrence of the motor phenotype, we observed a profoundly impaired dendritogenesis of neuroblasts in the hippocampal DG resulting in severely reduced survival of adult new-born neurons. Diminished neurogenesis concurred with a serotonergic deficit in the hippocampus as defined by reduced levels of serotonin (5-HT) 1B receptor, decreased 5-HT neurotransmitter levels, and a loss of serotonergic nerve terminals innervating the DG/CA3 subfield, while the number of serotonergic neurons in the raphe nuclei remained unchanged. Moreover, alpha-synuclein overexpression reduced proteins involved in vesicle release, in particular synapsin-1 and Rab3 interacting molecule (RIM3), in conjunction with an altered ultrastructural architecture of hippocampal synapses. Importantly, BAC alpha-synuclein rats showed an early anxiety-like phenotype consisting of reduced exploratory behavior and feeding. Taken together, these findings imply that accumulating alpha-synuclein severely affects hippocampal neurogenesis paralleled by impaired 5-HT neurotransmission prior to the onset of aggregation pathology and overt motor deficits in this transgenic rat model of PD.
EVALuna2:23681

Sex-specific pleiotropic changes in emotional behavior and alcohol consumption in human α-synuclein A53T transgenic mice during early adulthood - Kalinichenko, Liubov; Kohl, Zacharias; Mühle, Christiane; Hassan, Zurina; Hahn, Agnes; Schmitt, Eva Maria; Macht, Kilian; Stoyanov, Lyubomir; Moghaddami-Fara, Schayan; Bilbao Canalejas, Roberto; Eulenburg, Volker; Winkler, Jürgen; et al. (Journal of neurochemistry, 2024)
Point mutations in the α-synuclein coding gene may lead to the development of Parkinson's disease (PD). PD is often accompanied by other psychiatric conditions, such as anxiety, depression, and drug use disorders, which typically emerge in adulthood. Some of these point mutations, such as SNCA and A30T, have been linked to behavioral effects that are not commonly associated with PD, especially regarding alcohol consumption patterns. In this study, we investigated whether the familial PD point mutation A53T is associated with changes in alcohol consumption behavior and emotional states at ages not yet characterized by α-synuclein accumulation. The affective and alcohol-drinking phenotypes remained unaltered in female PDGF-hA53T-synuclein-transgenic (A53T) mice during both early and late adulthood. Brain region-specific activation of ceramide-producing enzymes, acid sphingomyelinase (ASM), and neutral sphingomyelinase (NSM), known for their neuroprotective properties, was observed during early adulthood but not in late adulthood. In males, the A53T mutation was linked to a reduction in alcohol consumption in both early and late adulthood. However, male A53T mice displayed increased anxiety- and depression-like behaviors during both early and late adulthood. Enhanced ASM activity in the dorsal mesencephalon and ventral hippocampus may potentially contribute to these adverse behavioral effects of the mutation in males during late adulthood. In summary, the A53T gene mutation was associated with diverse changes in emotional states and alcohol consumption behavior long before the onset of PD, and these effects varied by sex. These alterations in behavior may be linked to changes in brain ceramide metabolism.
CRIS-Team Scopus Importer:2024-02-16
Keywords: A53T; alcohol; ceramide; depression; neutral sphingomyelinase; Parkinson's disorder

Stem cell quiescence in the hippocampal neurogenic niche is associated with elevated transforming growth factor-β signaling in an animal model of huntington disease - Kandasamy, Mahesh; Couillard-Despres, Sebastien; Raber, Kerstin A.; Stephan, Michael; Lehner, Bernadette; Winner, Beate; Kohl, Zacharias; Rivera, Francisco J.; Nguyen, Huu Phuc; Riess, Olaf; Bogdahn, Ulrich; Winkler, Jürgen; et al. (Journal of Neuropathology and Experimental Neurology, 2010)
Cellular proliferation, differentiation, integration, and survival within the adult neural stem cell niche are altered under pathological conditions, but the molecular cues regulating the biology of this niche are mostly unknown. We examined the hippocampal neural stem cell niche in a transgenic rat model of Huntington disease. In this model, progressive cognitive deficits develop at the age of 9months, suggesting possible hippocampal dysfunction. We found a disease-associated progressive decline in hippocampal progenitor cell proliferation accompanied by an expansion of the pool of 5-bromo-2-deoxyuridine label-retaining Sox-2-positive quiescent stem cells in the transgenic animals. Increments in quiescent stem cells occurred at the expense of cAMP-responsive element-binding protein-mediated neuronal differentiation and survival. Because elevated levels of transforming growth factor-β1 (TGF-β1) impair neural progenitor proliferation, we investigated hippocampal TGF-β signaling and determined that TGF-β1 induces the neural progenitors to exit the cell cycle. Although phospho-Smad2, an effector of TGF-β signaling, is normally absent in subgranular stem cells, it accumulated progressively in Sox2/glial fibrillary acidic protein-expressing cells of the subgranular zone in the transgenic rats. These results indicate that alterations in neurogenesis in transgenic Huntington disease rats occur in successive phases that are associated with increasing TGF-β signaling. Thus, TGF-β1 signaling seems to be a crucial modulator of neurogenesis in Huntington disease and may represent a target for future therapy. © 2010 by the American Association of Neuropathologists, Inc.
CRIS-Team Scopus Importer:2024-08-07
Keywords: Adult neurogenesis; Huntington disease; Neural stem cells; Neuronal differentiation; Proliferation; Transforming growth factor-β

Structural Connectivity Patterns of Side Effects Induced by Subthalamic Deep Brain Stimulation for Parkinson's Disease - Kohl, Zacharias; Strotzer, Quirin D.; Kohl, Zacharias; Anthofer, Judith M.; Faltermeier, Rupert; Schmidt, Nils O.; Torka, Elisabeth; Greenlee, Mark W.; Fellner, Claudia; Schlaier, Juergen R.; Beer, Anton L. (Brain Connectivity, 2022)
Background: Tractography based on diffusion-weighted magnetic resonance imaging (DWI) models the structural connectivity of the human brain. Deep brain stimulation (DBS) targeting the subthalamic nucleus is an effective treatment for advanced Parkinson's disease, but may induce adverse effects. This study investigated the relationship between structural connectivity patterns of DBS electrodes and stimulation-induced side effects. Materials and Methods: Twenty-one patients with Parkinson's disease treated with bilateral subthalamic DBS were examined. Overall, 168 electrode contacts were categorized as inducing or noninducing depending on their capability for inducing side effects such as motor effects, paresthesia, dysarthria, oculomotor effects, hyperkinesia, and other complications as assessed during the initial programming session. Furthermore, the connectivity of each contact with target regions was evaluated by probabilistic tractography based on DWI. Finally, stimulation sites and structural connectivity patterns of inducing and noninducing contacts were compared. Results: Inducing contacts differed across the various side effects and from those mitigating Parkinson's symptoms. Although contacts showed a largely overlapping spatial distribution within the subthalamic region, they could be distinguished by their connectivity patterns. In particular, inducing contacts were more likely connected with supplementary motor areas (hyperkinesia, dysarthria), frontal cortex (oculomotor), fibers of the internal capsule (paresthesia), and the basal ganglia-thalamo-cortical circuitry (dysarthria). Discussion: Side effects induced by DBS seem to be associated with distinct connectivity patterns. Cerebellar connections are hardly associated with side effects, although they seem relevant for mitigating motor symptoms in Parkinson's disease. A symptom-specific, connectivity-based approach for target planning in DBS may enhance treatment outcomes and reduce adverse effects. Tractography based on diffusion-weighted magnetic resonance imaging has become a prominent technique for investigating the connectivity of human brain networks in vivo. However, the relationship between structural connections and brain function is still hardly known. The present study examined the relationship between adverse behavioral effects induced by deep brain stimulation (DBS) and tractography patterns in individual brains. The results suggest that DBS-based side effects depend on the structural connections of electrode contacts rather than their location. Network-based target planning in DBS may improve treatment by avoiding side effects. Moreover, the adopted approach may serve as a paragon for investigating structure/function relationships.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Deep brain stimulation; Diffusion tractography; Parkinson's disease; Structure/function relationship; Subthalamic nucleus

Synchronized sensor insoles for clinical gait analysis in home-monitoring applications - Roth, Nils; Martindale, Christine; Gaßner, Heiko; Kohl, Zacharias; Klucken, Jochen; Eskofier, Björn (Walter de Gruyter GmbH, 2018)
Wearable sensor systems are of increasing interest in clinical gait analysis. However, little information about gait dynamics of patients under free living conditions is available, due to the challenges of integrating such systems unobtrusively into a patient’s everyday live. To address this limitation, new, fully integrated low power sensor insoles are proposed, to target applications particularly in home-monitoring scenarios. The insoles combine inertial as well as pressure sensors and feature wireless synchronization to acquire biomechanical data of both feet with a mean timing offset of 15.0 μs. The proposed system was evaluated on 15 patients with mild to severe gait disorders against the GAITRite® system as reference. Gait events based on the insoles’ pressure sensors were manually extracted to calculate temporal gait features such as double support time and double support. Compared to the reference system a mean error of 0.06 s ±0.06 s and 3.89 % ±2.61 % was achieved, respectively. The proposed insoles proved their ability to acquire synchronized gait parameters and address the requirements for home-monitoring scenarios, pushing the boundaries of clinical gait analysi
Keywords: Double support; Home-monitoring; Gait; Synchronization; Insole

Technical Validation of an Automated Mobile Gait Analysis System for Hereditary Spastic Paraplegia Patients - Martindale, Christine; Roth, Nils; Gaßner, Heiko; List, Julia; Regensburger, Martin; Eskofier, Björn; Kohl, Zacharias (IEEE Journal of Biomedical and Health Informatics, 2019)
Hereditary spastic paraplegias (HSP) represents a group of orphan neurodegenerative diseases with gait disturbance as the predominant clinical feature. Due to its rarity, research within this field is still limited. Aside from clinical analysis using established scales, gait analysis has been employed to enhance the understanding of the mechanisms behind the disease. However, state of the art gait analysis systems are often large, immobile and expensive. To overcome these limitations, this paper presents the first clinically relevant mobile gait analysis system for HSP patients. We propose an unsupervised model based on local cyclicity estimation and hierarchical hidden Markov models (LCE-hHMM). The system provides stride time, swing time, stance time, swing duration and cadence. These parameters are validated against a GAITRite® system and manual sensor data labelling using a cohort of 24 patients within 2 separate studies. The proposed system achieves a stride time error of -0.00 ± 0.09 s (correlation coefficient, r = 1.00) and a swing duration error of -0.67 ± 3.27 % (correlation coefficient, r = 0.93) with respect to the GAITRite® system. We show that these parameters are also correlated to the clinical spastic paraplegia rating scale (SPRS) in a similar manner to other state of the art gait analysis systems, as well as to supervised and general versions of the proposed model. Finally, we show a proof of concept for this system to be used to analyse alterations in the gait of individual patients. Thus, with further clinical studies, due to its automated approach and mobility, this system could be used to determine treatment effects in future clinical trials.<br
Keywords: Hidden Markov models; Diseases; Legged locomotion; Foot; Informatics; Estimation; Mobile gait analysis; hereditary spastic paraplegia; hidden Markov model; semi-supervised learning; cyclicity

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Marxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Gräf, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2019)
EVALuna2:203042

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Maxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Graef, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2018)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive degeneration of midbrain neurons (MBNs). Recent evidence suggests contribution of the adaptive immune system in PD. Here, we show a role for human T lymphocytes as cell death inducers of induced pluripotent stem cell (iPSC)-derived MBNs in sporadic PD. Higher Th17 frequencies were found in the blood of PD patients and increased numbers of T lymphocytes were detected in postmortem PD brain tissues. We modeled this finding using autologous co-cultures of activated T lymphocytes and iPSC-derived MBNs of sporadic PD patients and controls. After co-culture with T lymphocytes or the addition of IL-17, PD iPSC-derived MBNs underwent increased neuronal death driven by upregulation of IL-17 receptor (IL-17R) and NF kappa B activation. Blockage of IL-17 or IL-17R, or the addition of the FDA-approved anti-IL-17 antibody, secukinumab, rescued the neuronal death. Our findings indicate a critical role for IL-17-producing T lymphocytes in sporadic PD.
EVALuna2:35782

The role of Nav1.7 in human nociceptors: Insights from human induced pluripotent stem cell-derived sensory neurons of erythromelalgia patients - Meents, Jannis E.; Bressan, Elisangela; Sontag, Stephanie; Foerster, Alec; Hautvast, Petra; Rösseler, Corinna; Hampl, Martin; Schüler, Herdit; Goetzke, Roman; Le, Thi Kim Chi; Kleggetveit, Inge Petter; Le Cann, Kim; et al. (Pain, 2019)
The chronic pain syndrome inherited erythromelalgia (IEM) is attributed to mutations in the voltage-gated sodium channel (NaV) 1.7. Still, recent studies targeting NaV1.7 in clinical trials have provided conflicting results. Here, we differentiated induced pluripotent stem cells from IEM patients with the NaV1.7/I848T mutation into sensory nociceptors. Action potentials in these IEM nociceptors displayed a decreased firing threshold, an enhanced upstroke, and afterhyperpolarization, all of which may explain the increased pain experienced by patients. Subsequently, we investigated the voltage dependence of the tetrodotoxin-sensitive NaV activation in these human sensory neurons using a specific prepulse voltage protocol. The IEM mutation induced a hyperpolarizing shift of NaV activation, which leads to activation of NaV1.7 at more negative potentials. Our results indicate that NaV1.7 is not active during subthreshold depolarizations, but that its activity defines the action potential threshold and contributes significantly to the action potential upstroke. Thus, our model system with induced pluripotent stem cell-derived sensory neurons provides a new rationale for NaV1.7 function and promises to be valuable as a translational tool to profile and develop more efficacious clinical analgesics.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Action potential firing; Erythromelalgia; Induced pluripotent stem cells; Inherited pain syndrome; iPS cells; Nociceptor; Pain; Patch-clamp; Voltage-gated sodium channel

Transcriptome-pathology correlation identifies interplay between TDP-43 and the expression of its kinase CK1E in sporadic ALS - Krach, Florian; Batra, Ranjan; Wheeler, Emily C.; Vu, Anthony Q.; Wang, Ruth; Hutt, Kasey; Rabin, Stuart J.; Baughn, Michael W.; Libby, Ryan T.; Diaz-Garcia, Sandra; Stauffer, Jennifer; Pirie, Elaine; et al. (Acta Neuropathologica, 2018)
Sporadic amyotrophic lateral sclerosis (sALS) is the most common form of ALS, however, the molecular mechanisms underlying cellular damage and motor neuron degeneration remain elusive. To identify molecular signatures of sALS we performed genome-wide expression profiling in laser capture microdissection-enriched surviving motor neurons (MNs) from lumbar spinal cords of sALS patients with rostral onset and caudal progression. After correcting for immunological background, we discover a highly specific gene expression signature for sALS that is associated with phosphorylated TDP-43 (pTDP-43) pathology. Transcriptome-pathology correlation identified casein kinase 1 epsilon (CSNK1E) mRNA as tightly correlated to levels of pTDP-43 in sALS patients. Enhanced crosslinking and immunoprecipitation in human sALS patient- and healthy control-derived frontal cortex, revealed that TDP-43 binds directly to and regulates the expression of CSNK1E mRNA. Additionally, we were able to show that pTDP-43 itself binds RNA. CK1E, the protein product of CSNK1E, in turn interacts with TDP-43 and promotes cytoplasmic accumulation of pTDP-43 in human stem-cell-derived MNs. Pathological TDP-43 phosphorylation is therefore, reciprocally regulated by CK1E activity and TDP-43 RNA binding. Our framework of transcriptome-pathology correlations identifies candidate genes with relevance to novel mechanisms of neurodegeneration.
EVALuna2:35779

Unbiased and Mobile Gait Analysis Detects Motor Impairment in Parkinson's Disease - Klucken, Jochen; Barth, Jens; Kugler, Patrick; Schlachetzki, Johannes; Henze, Thore; Marxreiter, Franz; Kohl, Zacharias; Steidl, Ralph; Hornegger, Joachim; Eskofier, Björn; Winkler, Jürgen (PLoS ONE, 2013)
Motor impairments are the prerequisite for the diagnosis in Parkinson's disease (PD). The cardinal symptoms (bradykinesia, rigor, tremor, and postural instability) are used for disease staging and assessment of progression. They serve as primary outcome measures for clinical studies aiming at symptomatic and disease modifying interventions. One major caveat of clinical scores such as the Unified Parkinson Disease Rating Scale (UPDRS) or Hoehn&Yahr (H&Y) staging is its rater and time-of-assessment dependency. Thus, we aimed to objectively and automatically classify specific stages and motor signs in PD using a mobile, biosensor based Embedded Gait Analysis using Intelligent Technology (eGaIT). eGaIT consist of accelerometers and gyroscopes attached to shoes that record motion signals during standardized gait and leg function. From sensor signals 694 features were calculated and pattern recognition algorithms were applied to classify PD, H&Y stages, and motor signs correlating to the UPDRS-III motor score in a training cohort of 50 PD patients and 42 age matched controls. Classification results were confirmed in a second independent validation cohort (42 patients, 39 controls). eGaIT was able to successfully distinguish PD patients from controls with an overall classification rate of 81%. Classification accuracy increased with higher levels of motor impairment (91% for more severely affected patients) or more advanced stages of PD (91% for H&Y III patients compared to controls), supporting the PD-specific type of analysis by eGaIT. In addition, eGaIT was able to classify different H&Y stages, or different levels of motor impairment (UPDRS-III). In conclusion, eGaIT as an unbiased, mobile, and automated assessment tool is able to identify PD patients and characterize their motor impairment. It may serve as a complementary mean for the daily clinical workup and support therapeutic decisions throughout the course of the disease. © 2013 Klucken et al.
EVALuna2:25318

Wearable sensors objectively measure gait parameters in Parkinson's disease - Schlachetzki, Johannes; Barth, Jens; Marxreiter, Franz; Goßler, Julia; Kohl, Zacharias; Reinfelder, Samuel; Gaßner, Heiko; Aminian, Kamiar; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen (PLoS ONE, 2017)
Distinct gait characteristics like short steps and shuffling gait are prototypical signs commonly observed in Parkinson's disease. Routinely assessed by observation through clinicians, gait is rated as part of categorical clinical scores. There is an increasing need to provide quantitative measurements of gait, e.g. to provide detailed information about disease progression. Recently, we developed a wearable sensor-based gait analysis system as diagnostic tool that objectively assesses gait parameter in Parkinson's disease without the need of having a specialized gait laboratory. This system consists of inertial sensor units attached laterally to both shoes. The computed target of measures are spatiotemporal gait parameters including stride length and time, stance phase time, heel-strike and toe-off angle, toe clearance, and inter-stride variation from gait sequences. To translate this prototype into medical care, we conducted a cross-sectional study including 190 Parkinson's disease patients and 101 age-matched controls and measured gait characteristics during a 4x10 meter walk at the subjects' preferred speed. To determine intraindividual changes in gait, we monitored the gait characteristics of 63 patients longitudinally. Cross-sectional analysis revealed distinct spatiotemporal gait parameter differences reflecting typical Parkinson's disease gait characteristics including short steps, shuffling gait, and postural instability specific for different disease stages and levels of motor impairment. The longitudinal analysis revealed that gait parameters were sensitive to changes by mirroring the progressive nature of Parkinson's disease and corresponded to physician ratings. Taken together, we successfully show that wearable sensor-based gait analysis reaches clinical applicability providing a high biomechanical resolution for gait impairment in Parkinson's disease. These data demonstrate the feasibility and applicability of objective wearable sensor-based gait measurement in Parkinson's disease reaching high technological readiness levels for both, large scale clinical studies and individual patient care.
EVALuna2:33508

Wearable sensors provide objective gait parameters correlating to clinical scores in Parkinson’s disease - Gaßner, Heiko; Schlachetzki, Johannes; Marxreiter, Franz; Kohl, Zacharias; Barth, Jens; Goßler, Julia; Reinfelder, Samuel; Pasluosta, Cristian Federico; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen (89th Congress of the Deutschen Gesellschaft für Neurologie mit Fortbildungsakademie (DGN), 2016)